Chemical, pasting and sensory properties of tapioca grits from cassava mosaic diseaseresistant cassava varieties - Eke, J.; Achinewhu, S.C.; Sanni, Lateef O. (Hindawi Limited, 2010)
The study investigated the chemical, pasting and sensory properties of tapioca grits produced from wet starches from 39 different cassava varieties (36 varieties resistant to cassava mosaic disease [CMD] and three checks TMS 30572, 4(2) 1425 and 82/00058) planted in June 2004/2005 at the experimental farm of the International Institute of Tropical Agriculture, highrainfall Onne (Lat 4.4°N, Long 7.1°E, mean annual rainfall of 2,600 mm.), Rivers State, Nigeria. There were significant differences (P < 0.05) for chemical and functional properties of tapioca grits from different cassava varieties. Amylose content ranged from 18.30 to 22.95%, amylopectin content ranged from 77.05 to 81.70%, protein content ranged from 0.16 to 0.42%, sugar content ranged from 0.10 to 1.20%, starch damage ranged from 1.22 to 1.49%, pH values ranged from 4.25 to 6.15, moisture content ranged from 5.75% to 10.12%, ash content ranged from 0.19 to 0.67%, starch content ranged from 67.34 to 81.86%. There were significant differences (P < 0.05) in all the pasting properties of the tapioca grits from different CMD starches. The peak viscosity of pregelatinized tapioca ranged from 110.79 to 545.17 RVU, final viscosities for tapioca ranged from 87.00 to 281.38 RVU. Setback values and